2019
DOI: 10.1016/j.vetmic.2019.108489
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation and characterization of porcine enteric alphacoronavirus strain GDS04 via serial cell passage

Abstract: A B S T R A C TPorcine enteric alphacoronavirus (PEAV) is a newly identified swine enteropathogenic coronavirus that causes watery diarrhea in newborn piglets. In this study, an original, highly virulent PEAV strain GDS04 was serially passaged in Vero cells. The virus titers and sizes of syncytia increased gradually with the cell passages. Newborn piglets were orally inoculated with PEAV P15, P67 and P100. Compared with P15 and P67, P100 resulted in only mild clinical signs and intestinal lesions in piglets. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…SADS-CoV isolated from clinical samples has poor adaptability to cells in vitro. In this study, the SADS-CoV GDS04 P15 strain, which has been shown to cause cytopathic effects in Vero cells and has a high mortality rate of 87.5% in newborn piglets [ 40 ], was used for in vitro research. The primary target cells of SADS-CoV in vivo are porcine intestinal epithelial cells [ 2 , 3 , 5 , 6 ], so we investigated the replication and proliferation of SADS-CoV in IPI-FX cells, which are derived from porcine ileum epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SADS-CoV isolated from clinical samples has poor adaptability to cells in vitro. In this study, the SADS-CoV GDS04 P15 strain, which has been shown to cause cytopathic effects in Vero cells and has a high mortality rate of 87.5% in newborn piglets [ 40 ], was used for in vitro research. The primary target cells of SADS-CoV in vivo are porcine intestinal epithelial cells [ 2 , 3 , 5 , 6 ], so we investigated the replication and proliferation of SADS-CoV in IPI-FX cells, which are derived from porcine ileum epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…The SADS-CoV strain used in this study was the GDS04 P15 strain, obtained from a wild-type SADS-CoV strain after 15 consecutive passages in Vero cells. It was adapted to cell growth while retaining high pathogenicity in newborn piglets [ 40 ]. The cells used in this study were IPI-FX cells, derived from subcloning porcine ileum epithelial cells (IPI-2I) through limited serial dilutions, and were highly susceptible to various porcine CoVs [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEDV LAV candidates include FJzz1 (GenBank accession: MK288006.1) [ 84 ], SDSX16 (GenBank accession: MH117940.1) [ 85 ], CT (GenBank accession: MN114121.1) [ 86 ], YN (GenBank accession: KT021227.1) [ 87 ], and Zhejiang08 [ 88 ]. SADS-CoV LAV candidates include GDS04 [ 89 ] and CN/GDWT/2017 [ 90 ]. The degree of attenuation and immunogenicity of these LAV candidates were evaluated in neonatal or weaned pigs.…”
Section: Sec Vaccine Development In Chinamentioning
confidence: 99%
“…LAV candidates FJzz1-F200 (the 200th passage (P200)), SDSX16-P75 (P75), CT-P120 (P120), GDS04-P100 (P100), and GDWT-P83 (P83) were all Vero cell-attenuated LAV candidates. The oral inoculation of suckling piglets resulted in lower fecal viral shedding and viral loads in the intestinal tissues and no obvious histopathological lesions [ 84 , 85 , 86 , 89 , 90 ]. The potential protective efficacy of FJzz1-F200 and SDSX16-P75 were instead conjectured from the induction of cytokines in porcine intestinal epithelial cells and serum IgG and IgA antibody responses in vaccinated neonatal piglets [ 84 , 85 ].…”
Section: Sec Vaccine Development In Chinamentioning
confidence: 99%